Races of Fusarium oxysporum causing wilt in chickpea - serological and electrophoretic variability - and A.G. RAMACHANDRA REDDY1, DESAI SUSEELENDRA, Y.L. NENE (Indian Phytopathology, 2002)
The four physiologic races of Fusarium oxysporum f. sp. ciceri causing wilt of chickpea had close antigenic relationships. All the four races showed one prominent cross reaction band. Race 4 was different from races 1,2 and 3 with regard to electrophoretic protein banding pattern. It lacked most of the high molecular weight (approx. 63 kD) protein bands. Two bands with Rf values 0.31 and 0.3'3 were consistently observed in race 2 while a fraction with Rf 0.20 was seen only in race 3. A fraction with Rf value 0.64 was characteristic of race 4. All the four races has common patterns of catalases, esterases and peroxidases, except race 1 which exhibited one extra peroxidase band.